A γ‐glutamyl hydrolase lacking the signal peptide confers susceptibility to folates/antifolates in acute lymphoblastic leukemia cells. Issue 4 (24th January 2022) - Wang, Shuxuan; Chen, Yao; Fang, Houshun; Xu, Yan; Ding, Ming; Ma, Chunshuang; Lin, Yanyan; Cui, Zhiyan; Sun, Huiying; Niu, Qun; Sun, Shuzhang; Zhou, Bin‐Bing S.; et al.
Abstract : A key cofactor of several enzymes implicated in DNA synthesis, repair, and methylation, folate has been shown to be required for normal cell growth and replication and is the basis for cancer chemotherapy using antifolates. γ‐Glutamyl hydrolase (GGH) catalyzes the removal of γ‐polyglutamate tails of folylpoly‐/antifolylpoly‐γ‐glutamates to facilitate their export out of the cell, thereby maintaining metabolic homeostasis of folates or pharmacological efficacy of antifolates. However, the factors that control or modulate GGH function are not well understood. In this study, we show that intact GGH is not indispensable for the chemosensitivity and growth of acute lymphoblastic leukemia (ALL) cells, whereas GGH lacking N‐terminal signal peptide (GGH −ΔN ) confers the significant drug resistance of ALL cells to the antifolates MTX and RTX. In addition, ALL cells harboring GGH −ΔN show high susceptibility to the change in folates, and glycosylation is not responsible for these phenotypes elicited by GGH −ΔN . Mechanistically, the loss of signal peptide enhances intracellular retention of GGH and its lysosomal disposition. Our findings clearly define the in vivo role of GGH in ALL cells and indicate a novel modulation of the GGH function, suggesting new avenues for ALL treatment in future. Abstract : GGH plays an important role in maintaining metabolic homeostasis of folates or pharmacological efficacy of antifolates. We find that GGH lacking N ‐terminal signal peptide (GGH −ΔN ) confers the significant drug resistance of ALL cells to antifolates, and ALL cells harboring GGH −ΔN show high susceptibility to the change in folates. Our findings indicate a novel modulation of GGH function.